New paradigm in diatom omics and genetic manipulation. (April 2021) - Bhattacharjya, Raya; Tiwari, Archana; Marella, Thomas Kiran; Bansal, Hina; Srivastava, Shireesh
Graphical abstract: Highlights: Prediction of novel metabolic networks using 'multi omics' approach in diatoms. High throughput reconstruction of eco-evolutionary trends in microbial interaction. Genome manipulation involving gene driven engineering and editing techniques. Integration of omics data using systems biology approach. Abstract: Diatoms are one of the most heterogeneous eukaryotic plankton known for regulating earth's biogeochemical cycles and maintaining the marine ecosystems ever since the late Eocene epoch. The advent of multidisciplinary omics approach has both epitomized and revolutionized the nature of their chimeric genetic toolkit, ecophysiology, and metabolic adaptability as well as their interaction with other communities. In addition, advanced functional annotation of transcriptomic and proteomic data using cutting edge bioinformatics tools together with high-resolution genome-scale mathematical modeling has effectively proven as the catapult in solving genetic bottlenecks in microbial as well as diatom exploration. In this review, a corroborative summation of the robust work done in manipulating, engineering, and sequencing of the diatom genomes besides underpinning the holistic application of omics in transcription and translation has been discussed in order to shrewd their multifarious novel potential in the field of biotechnology and provide an insight into their dynamic evolutionary relevance.